2022
DOI: 10.3389/fped.2021.780166
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tracheal Occlusion Increases Lung Basal Cells via Increased Yap Signaling

Abstract: Fetal endoscopic tracheal occlusion (FETO) is an emerging surgical therapy for congenital diaphragmatic hernia (CDH). Ovine and rabbit data suggested altered lung epithelial cell populations after tracheal occlusion (TO) with transcriptomic signatures implicating basal cells. To test this hypothesis, we deconvolved mRNA sequencing (mRNA-seq) data and used quantitative image analysis in fetal rabbit lung TO, which had increased basal cells and reduced ciliated cells after TO. In a fetal mouse TO model, flow cyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Novel therapeutics, such as amniotic fluid derived extracellular vesicles can promote prenatal lung maturation in CDH animal models (59, 60). Future studies could explore how such therapeutics can rescue CDH phenotypes in our in vitro model and large animal models before clinical testing in CDH patients when applied alone or in combination with FETO (61). Lastly, TA BSCs derived from larger CDH patient cohorts, in combination with genetic mapping of patient-specific de novo mutations, is warranted to deepen our understanding of the pathogenesis of lung defects in CDH.…”
Section: Discussionmentioning
confidence: 99%
“…Novel therapeutics, such as amniotic fluid derived extracellular vesicles can promote prenatal lung maturation in CDH animal models (59, 60). Future studies could explore how such therapeutics can rescue CDH phenotypes in our in vitro model and large animal models before clinical testing in CDH patients when applied alone or in combination with FETO (61). Lastly, TA BSCs derived from larger CDH patient cohorts, in combination with genetic mapping of patient-specific de novo mutations, is warranted to deepen our understanding of the pathogenesis of lung defects in CDH.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling pathway is a conserved mechanosensitive pathway that regulates cell proliferation through response to mechanical stimuli and is critical for organ development [34][35][36][37][38][39][40] . The Hippo signaling pathway has been reported to be dysregulated in rodent models of CDH 39,[41][42][43] . Serapiglia et al reported that fetal mouse with conditional depletion of Yap from the lung epithelium had reduced lung basal cell population in comparison to fetal lungs from wild-type mouse 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway has been reported to be dysregulated in rodent models of CDH 39,[41][42][43] . Serapiglia et al reported that fetal mouse with conditional depletion of Yap from the lung epithelium had reduced lung basal cell population in comparison to fetal lungs from wild-type mouse 42 . Kahnamoui et al demonstrated that the Hippo signaling effector protein Yap is inactive in nitrofen-induced hypoplastic lungs in comparison to control lungs 43 .…”
Section: Discussionmentioning
confidence: 99%